What does the mediodorsal thalamus do? - Mitchell, Anna S.; Chakraborty, Subhojit (Frontiers in Systems Neuroscience, 2013)
Dense amnesia can result from damage to the medial diencephalon in humans and in animals. In humans this damage is diffuse and can include the mediodorsal nuclei of the thalamus. In animal models, lesion studies have confirmed the mediodorsal thalamus (MD) has a role in memory and other cognitive tasks, although the extent of deficits is mixed. Anatomical tracing studies confirm at least three different subgroupings of the MD: medial, central and lateral, each differentially interconnected to the prefrontal cortex. Moreover, these subgroupings of the MD also receive differing inputs from other brain structures, including the basal ganglia thus the MD subgroupings form key nodes in interconnected frontal-striatal-thalamic neural circuits, integrating critical information within the prefrontal cortex. We will provide a review of data collected from non-human primates and rodents after selective brain injury to the whole of the MD as well as these subgroupings to highlight the extent of deficits in various cognitive tasks. This research highlights the neural basis of memory and cognitive deficits associated with the subgroupings of the MD and their interconnected neural networks. The evidence shows that the MD plays a critical role in many varied cognitive processes. In addition, the MD is actively processing information and integrating it across these neural circuits for successful cognition. Having established that the MD is critical for memory and cognition, further research is required to understand how the MD specifically influences these cognitive processing carried out by the brain.